Incidence and recognition of acute respiratory distress syndrome in a UK intensive care unit. Issue 11 (22nd August 2016) - Summers, Charlotte; Singh, Nanak R; Worpole, Linda; Simmonds, Rosalind; Babar, Judith; Condliffe, Alison M; Gunning, Kevin E; Johnston, Andrew J; Chilvers, Edwin R
Abstract : The reported incidence of ARDS is highly variable (2.5%–19% of intensive care unit (ICU) patients) and varies depending on study patient population used. We undertook a 6-month, prospective study to determine the incidence and outcome of ARDS in a UK adult University Hospital ICU. 344 patients were admitted during the study period, of these 43 (12.5%) were determined to have ARDS. Patients with ARDS had increased mortality at 28 days and 2 years post-diagnosis, and there was under-recognition of ARDS in both medical records and death certificattion. Our findings have implications for critical care resource planning.